The Effect of Edmodo-Based E-Learning toward Participation and Understanding of Elementary School Teacher Candidate - Hanifah Nuryani; Haryanto Haryanto; Setyo Eko Atmojo (UIN Siber Syekh Nurjati Cirebon, 2020)
AbstractThis study aims to determine the effect of Edmodo-based E-learning on the participation and understanding of elementary school teacher candidate in science 1 biology courses. This study used a quasi-experimental method using a non-equivalent control group design. The sample of this study was 49 elementary school teacher candidates in semester 2 of PGRI Yogyakarta University. The data collection technique used a participatory questionnaire instrument and a pretest-posttest comprehension test. The results of the Independent Sample t-Test show that the value of Sig. for the participation variable of 0.004 <0.05 and the Sig. for the understanding variable of 0.005 <0.05. While, the MANOVA test results show the value of Sig. for the participation variable of 0.004 <0.05 and the Sig. for the understanding variable of 0.005 <0.05. This means that there are differences in the increase in participation and understanding of elementary school teacher candidate after using Edmodo-based E-learning. In addition, the application of Edmodo-based E-learning also has a positive effect on the participation and understanding of elementary school teacher candidate on science topics. Edmodo-based e-learning makes elementary school teacher candidates more active in participating and easier in understanding science lecture material 1.Keywords: edmodo-based e-learning, participation of elementary school teacher candidate, natural science understanding.Â Â AbstrakPenelitian ini bertujuan untuk mengetahui pengaruh E-learning berbasis Edmodo terhadap partisipasi dan pemahaman calon guru Sekolah Dasar pada mata kuliah IPA 1 materi biologi. Penelitian ini menggunakan metode eksperimen semu dengan menggunakan desain penelitian non-equivalent control group design. Sampel penelitian ini adalah 49 calon guru Sekolah Dasar semester 2 Universitas PGRI Yogyakarta. Teknik pengumpulan data menggunakan instrumen angket partisipasi dan tes pemahaman melalui pretest-posttest. Hasil Uji Independent Sample t-Test menunjukkan nilai Sig. untuk variabel partisipasi sebesar 0.004 < 0.05 dan nilai Sig. untuk variabel pemahaman sebesar 0.005 < 0.05. Sedangkan hasil uji MANOVA menunjukkan nilai Sig. untuk variabel partisipasi sebesar 0.004 < 0.05 dan nilai Sig. untuk variabel pemahaman sebesar 0.005 < 0.05. Hal ini berarti bahwa terdapat perbedaan peningkatan partisipasi dan pemahaman calon guru Sekolah Dasar setelah menggunakan E-learning berbasis Edmodo. Selain itu, penerapan E-learning berbasis Edmodo juga berpengaruh positif terhadap partisipasi dan pemahaman calon guru Sekolah Dasar pada topik IPA. E-learning berbasis Edmodo menjadikan calon guru Sekolah Dasar lebih aktif dalam berpartisipasi dan lebih mudah dalam memahami materi perkuliahan IPA 1.Kata kunci: e-learning berbasis edmodo, partisipasi calon guru SD, pemahaman IPA.